Faktor-Faktor Yang Memengaruhi Perilaku Penggunaan Fitur PayLater pada Aplikasi Shopee (SPayLater) Dengan Model UTAUT2 - Oca Amartya Awdes; Firman Surya; Zahara (Accounting Information System, Taxes and Auditing Journal (AISTA Journal), 2022)
This study aims to determine the factors that can influence the behavior of using the paylater feature in the Shopee application (SPayLater) using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model. The factors used in this study are performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, and habits. Respondents of this study were Politeknik Negeri Padang students who used the paylater feature in the Shopee application (SPayLater). The data used is primary data obtained using a survey technique by distributing online questionnaires via google form. Analysis of research data using multiple linear regression analysis with the help of the IBM SPSS version 25 program. The results showed that performance expectancy and habits had a positive effect on the behavior of using the Paylater feature on the Shopee application (SPayLater), while the factors of effort expectancy, social influence, facilitating conditions, hedonic motivation, and price value do not have a positive effect on the behavior of using the paylater feature on the Shopee application (SPayLater ).